PENGARUH KUALITAS PELAYANAN DAN CITRA PERUSAHAAN TERHADAP KEPUASAN NASABAH - Sari, Dessy Handa; Ningsih, Sri; Agustin, Kety Lulu (LPPM STIE Muhammadiah Bandung, 2023)
This study aims to determine the effect of service quality and corporate image on customer satisfaction at PT Pegadaian (Persero) UPC Pasar Buton. The method used is a quantitative method. The dependent variable in this research is Customer Satisfaction and the independent variable is Service Quality and Company Image. The data analysis method used multiple linear regression, the results of the analysis showed that the service quality variable had a significant effect on customer satisfaction, and corporate image had a significant effect on customer satisfaction. Based on the results of the simultaneous test (F test) service quality and company image have a significant effect on customer satisfaction. And the results of the t-test of the service quality variable have a positive and significant effect on customer decisions with a significantly smaller positive level. The corporate image variable has a positive and significant effect on customer satisfaction with a positive significant level less than.